Amplified cold transduction in native nociceptors by M-channel inhibition - Vetter, Irina; Hein, Alexander; Sattler, Simon; Heßler, Sabine; Touska, Filip; Bressan, Elisangela; Parra, Andres; Hager, Ulrich; Leffler, Andreas; Boukalova, Stepana; Nissen, Matthias; Lewis, Richard J.; et al. (The Journal of Neuroscience, 2013)
Topically applied camphor elicits a sensation of cool, but nothing is known about how it affects cold temperature sensing. We found that camphor sensitizes a subpopulation of menthol-sensitive native cutaneous nociceptors in the mouse to cold, but desensitizes and partially blocks heterologously expressed TRPM8 (transient receptor potential cation channel subfamily M member 8). In contrast, camphor reduces potassium outward currents in cultured sensory neurons and, in cold nociceptors, the cold-sensitizing effects of camphor and menthol are additive. Using a membrane potential dye-based screening assay and heterologously expressed potassium channels, we found that the effects of camphor are mediated by inhibition of Kv7.2/3 channels subtypes that generate the M-current in neurons. In line with this finding, the specific M-current blocker XE991 reproduced the cold-sensitizing effect of camphor in nociceptors. However, the M-channel blocking effects of XE991 and camphor are not sufficient to initiate cold transduction but require a cold-activated inward current generated by TRPM8. The cold-sensitizing effects of XE991 and camphor are largest in high-threshold cold nociceptors. Low-threshold corneal cold thermoreceptors that express high levels of TRPM8 and lack potassium channels are not affected by camphor. We also found that menthol-like camphor-potently inhibits Kv7.2/3 channels. The apparent functional synergism arising from TRPM8 activation and M-current block can improve the effectiveness of topical coolants and cooling lotions, and may also enhance TRPM8-mediated analgesia. © 2013 the authors.
CRIS-Team Scopus Importer:2021-07-19